Pharmacokinetic evaluation of the aripiprazole (once-monthly) injection for the treatment of bipolar disorder. (3rd October 2018) - Hebbrecht, Kaat; Morrens, Manuel; Neels, Hugo; Roosens, Laurence; Sabbe, Bernard G. C.
ABSTRACT: Introduction : Bipolar disorder is a severe, chronic psychiatric disorder with a need for long-term treatment. Patient nonadherence is frequent and poses a major problem in maintenance therapy. Aripiprazole once-monthly long-acting injectable (AOM LAI) is a recently US Food and Drug Administration-approved treatment option for maintenance therapy that could be of great value. Areas covered : This paper reviews the pharmacokinetic, efficacy and safety data for AOM LAI in bipolar disorder. Expert opinion : AOM LAI is a safe and efficacious treatment option in the maintenance therapy of bipolar I disorder. However, further research is still needed to determine the position of AOM LAI relative to other available treatment options.